Anatomage Table 6. Issue 2 (3rd April 2019) - Allen, Melanie A.; Kirkpatrick, Niki; Agosto, Elizabeth R.
Abstract: Anatomage Table 6, launched in fall 2018, is the latest software for users of the Anatomage Virtual Dissection Table. Anatomage Table 6 comprises numerous virtual anatomy dissection and study tools for use by anatomy students and instructors. This review provides an overview and assessment of Anatomage Table 6's primary tools and advanced navigation features.